Inovasi Produk Brownies Dengan Bahan Tambahan Selai Nanas Subang Terhadap Daya Terima Konsumen - ., Erliana; Sudono, Agus; H. Rumayar, Christian (Universitas Pendidikan Indonesia, 2016)
Pineapple fruits are main commodity harvested by people in Kabupaten Subang.But inovation of this fruits in it manufacture has not diverse and keep abreast ofculinary. Therefore, to created new product of processed pineapple fruits, researcher have inovation to make Brownies Nanas, to raise the value of selling product and to give job opportunities in developt processed pineapple fruits in Kabupaten Subang.Based on that reasons, this research divide to three research purpose, that is: (1) Knowing formulated Brownies recipe with addition pineapple jam; (2) Knowing technique of processing Brownies with addition pineapple jam; and (3) Knowing acceptance consumer toward Brownies with addition pineapple jam.This research using two variable, x variable is Brownies withaddition pineapple jam and y variable is acceptance consumer toward product. The methods of this research using experimental method. Organoleptik test is used toward six consentration of Pineapple Brownies formulation contains different degree of pineapple jam to 15 panelist expert and picked one choosen product. And then tested again toward 100 consumer panelist to testing acceptance consumer. After that, analysis of DKBM nutrients can be done by researcher. SPSS 22 is used to do analysis methods of this research, using ANOVA test, LSD with Organoleptik test, and T experimentwith Hedonik test with acceptance consumer. Outcome of this research explain that Pineapple Brownies with addition 125% concentrated pineapple jam (BP2) can be accepted by panelist expert in Organoleptik and Hedonik test. In acceptance consumer test toward 100 responden, BP2 products can be accepted in 4 in 5 scale (like). In DKBM nutrients analysis, this Brownies Nanas product contains 801 Kkal.